Early Warning Value of ASL-MRI to Estimate Premorbid Variations in Patients With Early Postoperative Cognitive Dysfunctions - Du, Xue; Gao, Yan; Liu, Su; Zhang, Jingya; Basnet, Diksha; Yang, Junjun; Liu, Jiehui; Deng, Yijie; Hu, Jiayong; Wang, Peijun; Liu, Jianhui (Frontiers in Aging Neuroscience, 2021)
Postoperative cognitive dysfunction (POCD) is a general complication following cardiac and major non-cardiac surgery amongst the elderly, yet its causes and mechanisms are still unknown. The present study aimed to detect whether regional cerebral blood flow (CBF) is altered in brain before surgery in POCD patients comparing with non-POCD (NPOCD) patients, thus, CBF variation may potentially predict the occurrence of early POCD.50 patients scheduled for spinal stenosis surgery were enrolled in the study. All study participants completed a battery of neuropsychological tests by a well-trained neuropsychologist before the surgery and 1 week after the surgery. POCD was defined when the preoperative to postoperative difference of at least two of the neuropsychological tests’ |Z|-scores with reference to a control group exceeded 1.96. Pulsed arterial spin-labeling (ASL) MRI was scanned at least one day before surgery. The ASLtbx toolkit and SPM12 were applied to preprocess and correct the images, which were then normalized to the MNI brain template space to obtain standardized cerebral perfusion images.POCD was identified in 11 out of 50 patients (22%). The CBF of the right superior temporal lobe, right and left middle cingulate gyrus and the right hippocampus and parahippocampal gyrus in POCD group was lower than that in NPOCD group (P < 0.001). The CBF of the pars triangularis of inferior frontal grus in POCD group was higher than that in NPOCD group (P < 0.001).These preliminary findings suggest that CBF premorbid alterations may happen in cognitively intact elderly patients that develop early POCD. Alterations of preoperative CBF might be a bio-marker for early POCD that can be detected by noninvasive MRI scan.